Pengaruh Usaha Koordinasi, Integrasi Strategis, Orientasi Pasar, Dan Inovasi Produk Terhadap Kinerja Pemasaran Pada Toko Bombay Textile Indonesia - Patrick Wangsa dan Rina Adi Kristianti (Universitas Tarumanagara, 2019)
Every monthly sales value in Stores Bombay Textile Indonesia in the year continued to increase in 2016, although in the sector that data showed sales decline. The purpose of this research is to know the effect of coordination effort, strategic integration, market orientation, and product innovation simultaneously on marketing performance At Bombay Textile Indonesia Store. The research method used in this research using explanotory reseach type or research form through associative research, survey method is data collection conducted on the object in the field by taking samples from a population by using questionnaires. The number of samples in the study amounted to 105 respondents. Data analysis technique used multiple linear regression analysis.The results showed that partially coordination efforts have a positive effect on marketing performance. Strategic integration positively affects marketing performance. Product innovation has a positive effect on marketing performance Market orientation has a positive effect on marketing performance. Simultaneously coordination efforts, strategic integration, market orientation, and product innovation simultaneously affect the marketing performance At Bombay Textile Indonesia